A study of the incidence of retinopathy of prematurity in a tertiary care centre in Karnataka - R., Manjunathaswmy; Rao, Anjana H.; Hegade, Vinayaka P.; Kumar, Pradeep; Patil, Ravindra B. (International Journal of Contemporary Pediatrics, 2021)
Background: Retinopathy of prematurity is a preventable cause of childhood blindness. Proper understanding of the classification, risk factors and treatment methods is a must in tackling this disease. The aim of this study was to know the incidence of ROP in preterm infants in a tertiary care centre and to improvise the selection criteria in future in Indian babies. Methods: A retrospective study of all infants admitted to the NICU from 2016 to 2018 who met the criteria for ROP screening were included in the study. Examination of the eyes was done by a trained technician using a Ret Cam digital imaging in collaboration with KIDROP, Narayana Nethralaya and later interpreted by trained ophthalmologists using the concept of teleopthalmology. Babies were followed up and screened accordingly. Qualified infants were treated with argon laser photocoagulation within 48h of diagnosis. They were followed until the disease was successfully treated. Results: In current study, incidence of ROP was found to be 10.2%. The gestational age ranged from 28-36 weeks with a mean of 30.5±1.5 weeks. In current study, the most prevalent prenatal risk factor was multiple gestation and postnatal risk factors was anemia, low birth weight ,low gestational age and the use of oxygen therapy. Conclusions: Screening for ROP, in India, should be performed in all preterm neonates who are born <34 weeks gestation and/or <1800 grams birth weight; as well as in babies 34-36 weeks gestation or 1800-2000 grams birth weight if they have risk factors for ROP.